2010
DOI: 10.1167/iovs.09-4888
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Peripapillary Retinal Nerve Fiber Distribution in Normal Young Adults

Abstract: PURPOSE. To determine the anatomic variations in the peripapillary retinal nerve fiber layer (RNFL) thickness distribution and the relationship between these anatomic variations and other ocular variables. METHODS. A complete ophthalmic examination, including measurement of visual acuity, refraction, and axial length, was performed on 269 subjects with no ophthalmic abnormalities. Further, fundus photographs and optic disc cube scans of the subjects' eyes were obtained with a fundus camera and spectral domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 30 publications
6
63
1
Order By: Relevance
“…Their values for CDRs were 0.47 (average) and 0.47 (vertical), which were similar to the current study. Hong et al, 17 who examined 269 (96% male) normal Korean military personnel aged 19 to 26 years, found an average RNFL thickness of 98.2±8.6 mm, which is very similar to our value in males of 98.8 ± 9.8 mm and slightly less than our value for East Asians of 100.1 ± 9.4 mm. This study did not present optic disc data.…”
Section: Eyesupporting
confidence: 88%
See 2 more Smart Citations
“…Their values for CDRs were 0.47 (average) and 0.47 (vertical), which were similar to the current study. Hong et al, 17 who examined 269 (96% male) normal Korean military personnel aged 19 to 26 years, found an average RNFL thickness of 98.2±8.6 mm, which is very similar to our value in males of 98.8 ± 9.8 mm and slightly less than our value for East Asians of 100.1 ± 9.4 mm. This study did not present optic disc data.…”
Section: Eyesupporting
confidence: 88%
“…[16][17][18][19][20] The largest OCT study to date is by Knight et al, 16 who presented data on 271 normal subjects aged 18-84 years. They had an average RNFL thickness of 94.0 mm (SE 0.6) (adjusted for age and disc area) in their multi-ethnic population.…”
Section: Eyementioning
confidence: 99%
See 1 more Smart Citation
“…14 It has been reported that the thickness of the supratemporal and infratemporal RNFL bundles, and the position of the peak RNFL thickness are shifted in eyes with longer axial lengths (ALs). 15,16 Thus, the supratemporal RNFL bundle is shifted closer to the fovea in highly myopic eyes than in low myopic eyes (Fig. 1).…”
mentioning
confidence: 91%
“…[11][12][13] This shift of the myopic RNF bundle can lead to paracentral NFLDs in glaucomatous myopic eyes because of its location. We have reported that the trajectory of the temporally-thick retinal nerve fiber bundles and retinal arteries can be described by a second degree polynomial equation.…”
mentioning
confidence: 99%